The patterns of nitrogen fixation in haloalkaliphilic phototrophic communities of Kulunda Steppe soda lakes (Altai, Russia). Issue 11 (25th October 2019) - Samylina, Olga S; Namsaraev, Zorigto B; Grouzdev, Denis S; Slobodova, Natalia V; Zelenev, Vladimir V; Borisenko, Gennadii V; Sorokin, Dimitry Y
ABSTRACT: Nitrogen fixation (NF) of phototrophic communities was studied in a number of soda lakes with a wide range of salinity (25–400 g/l) located in Kulunda Steppe (Altai, Russia) during several summer seasons (2011–2016). The phototrophic communities were represented by the algal-bacterial Ctenocladus communities or cyanobacterial biofilms dominated by heterocystous and non-heterocystous cyanobacteria and purple sulfur bacteria Ectothiorhodospira sp. (up to 210 g/l) and endoevaporitic Euhalothece communities dominated by the extremely salt-tolerant unicellular cyanobacterium Euhalothece sp. and Ectothiorhodospira sp. (above 350 g/l). Salinity was the major factor influencing the composition and NF potential of the phototrophic communities. The communities dominated by vegetative heterocystous cyanobacteria exhibited light-independent NF at total salinity up to 60 g/l. The communities dominated by non-heterocystous cyanobacteria exhibited light-dependent NF in a range of 55–100 g/l, but it was significantly suppressed at 100 g/l. At 160–200 g/l the dark heterotrophic NF was a prevailing process if communities didn't contain Euhalothece sp. At salt-saturating ranges above 350 g/l, light-dependent NF associated with the Euhalothece communities was detected. A statistically significant positive correlation between the NF and diurnal light intensity was found in all samples of communities dominated by non-heterocystous cyanobacteria in contrast to communities dominated by heterocystous cyanobacteria with insignificant correlation coefficients. Abstract : An analysis of the nitrogen-fixing activity and composition of the haloalkaliphilic phototrophic communities in soda lakes of the Kulunda Steppe in the salinity range of 25-400 g/l.